Mind the blind spot: lessons from fungal community sequencing in a plant–soil feedback experiment - Mengshuai Liu; Jose G. Maciá-Vicente; Jasper van Ruijven; Wopke van der Werf; Zhenling Cui; Fusuo Zhang; Chunxu Song; Liesje Mommer (CABI Agriculture and Bioscience)
Abstract Background Plant–soil feedback (PSF) has gained increasing interest in agricultural systems. An important question is whether PSF differs between different cropping systems. Few attempts have yet been made to identify the pathogen species involved in negative PSF. Here, we hypothesize that the strength of negative PSF experienced by a crop species is determined by the relative abundance of host-specific soil-borne pathogenic fungi, that is in turn driven by the crop’s relative abundance (in time). Methods We performed a PSF experiment, with different soils originating from three cropping systems in the North China Plain and three crop species (wheat, maize, soybean) in a full factorial design. Soil fungal community composition and relative abundance of fungal (pathogen) species in each treatment was identified by metabarcoding using ITS (Internal Transcribed Spacer) sequencing. Results PSF ranged from negative for wheat, neutral to negative for soybean and neutral to positive for maize, but the former density of a crop in a particular cropping system did not affect the strength of PSF experienced by each of the three. No relationships between fungal pathogen abundance and PSF were found, but we did find a surprisingly large enrichment across steps of the experiment of Chaetomium spp., a known cellulose-degrading fungus. This may be explained by addition of filter paper on the bottom of the pots. Conclusions Our results suggest that the strength of PSF in these crops is not related to the relative abundance of specific fungal pathogens. However, we cannot rule out that our results were affected by the high abundance of one particular cellulose-degrading fungus. This highlights both the need to stop the practice of using filter paper in pot experiments, as well as the relevance of assessing the identity, relative abundance and potential functions of fungal taxa in PSF experiments.